Specific Features of Global Finance Strategies of Multinational Corporations in World Chemical Industry - V. I. Dzetsina (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
Today’s situation in foreign economic relations can be characterized as unstable, which becomes evident through trade wars, numerous sanctions and other attempts to impact the real sector of economy on the political level. Changes in foreign trade policy of many countries and slump in globalization make multinational corporations of chemical industry adapt quickly to the changing conditions. Sectoral specificity is an acute necessity to introduce advanced digital technologies, though many multinationals are still on the stage of technological innovation. The article estimates the effect of transformation taking place in the industry in global and regional scale, which can be used to correct state influence and implement forecasts of the global chemical industry development. The author came to the conclusion about the drop in investment activity, its concentration in the country of location and liability to demands of local strategy of chemical industry development. The author puts forward an approach to the appraisal of global finance strategies of multinationals through concrete identification of the research subject and choice of three most important vectors: investment strategy, strategy of shaping finance resources and taxation strategy.